Methodological Possibilities of Using Media Educational Technologies to Increase the Professional Activity of Future Primary School Teachers - Ismoilovich, Davronov Dilshod (European Journal of Life Safety and Stability (2660-9630), 2021)
The article provides analytical coverage of didactic requirements for modern pedagogy, students' professional training in media education technologies, pedagogical principles of media education, effective innovative methods and didactic recommendations. It have been scientifically analyzed methodological possibilities of using media educational technologies in increasing the professional activity of future primary school teachers.